Accuracy of clinical assessment of heart murmurs by office based (general practice) paediatricians. Issue 5 (1st November 1999) - Haney, Isabel; Ipp, Moshe; Feldman, William; McCrindle, Brian W
Abstract : AIM: To determine the diagnostic accuracy of physical examination by office based (general practice) paediatricians in the evaluation of heart murmurs. DESIGN: Each of 30 office based paediatricians blindly examined a random sample of children with murmurs (43% of which were pathological). Sensitivity and specificity were calculated and were related to paediatricians' characteristics. RESULTS: Mean (SD) sensitivity was 82 (24)% with a mean specificity of 72 (24)% in differentiating pathological from innocent murmurs, with further investigations requested for 54% of assessments. The addition of a referral strategy would have increased mean sensitivity to 87 (20)% and specificity to 98 (8)%. Diagnostic accuracy was not significantly related to the paediatricians' age, education or practice characteristics, but was related to referral practices and confidence in assessment. CONCLUSIONS: Diagnostic accuracy of clinical assessment of heart murmurs by office based paediatricians is suboptimal, and educational strategies are needed to improve accuracy and reduce unnecessary referrals and misdiagnosis.